A Note on the Use of the Two-Stage Least Squares Estimator in Financial Models - Lloyd, William P. (Journal of Financial and Quantitative Analysis, 1975)
Financial or capital market theory is intimately concerned with the concept of a general equilibrium. But most of the empirical work in finance has been concerned with the estimation of single-equation ordinary least squares cross-sectional models. One way of capturing some of the flavor of a general equilibrium is to use a simultaneous equation valuation model. Thus the value or the return on a security can be determined simultaneously in relationship to and in competition with the other securities in the system. Simkowitz and Jones [4] have recently described how the methodology could be used. Simkowitz and Logue [5] have recently performed a study using this methodology.